Political Public Relations as a Tool for Combating Vote buying in Nigeria for Development Purposes - Chiakaan, Jacob Gbaden; Egbulefu, Chamberlain Chinsom; Kpera, Wombu Richard; Kaigama, Pius Kwapsoni (UI Scholars Hub, 2021)
The main aim of the study is to identify political public relations approaches that can be applied by the government and other bodies responsible for conducting elections in Nigeria to mitigate and eliminate vote buying. The study adopted a qualitative approach in the contextual analysis of data collected specifically from secondary sources. The results revealed that vote buying has become synonymous with elections in Nigeria. After reviewing some related empirical studies, several factors responsible for vote buying in Nigeria have been identified, including poverty, lack of education, high cost of buying forms to contest elections, and many others. Moreover, where votes are purchased by political parties and candidates, the essence of elections as a credible leadership selection process is often put on the line. Another disadvantage associated with vote buying is that the practice can produce leaders who have questionable characters and are not the actual choice of the masses. Where this practice is condoned, this can lead to bad governance and, ultimately, underdevelopment. Therefore, the study recommends good governance and enough sensitization campaigns as political public relations strategies of combating vote buying in Nigeria.